Direct and Indirect Analysis of the Elevational Shift of Larch Budmoth Outbreaks Along an Elevation Gradient - Rozenberg, Philippe; Pâques, Luc; Huard, Frédéric; Roques, Alain (Frontiers in Forests and Global Change, 2020)
Larch budmoth (LBM) periodically defoliates alpine stands of European larch during vast outbreaks occurring generally at 8-10 year intervals. LBM outbreaks recently declined and the ongoing global warming has been pointed out as a possible cause of this decline. We reconstructed the recent history of LBM outbreaks at different elevations along a larch altitudinal gradient in the French Alps using direct and indirect observations based on tree-ring width and density analysis, and compared it with local climatic data. We found that LBM outbreaks time-series were better reconstructed with latewood density than with ring width. We also found that there was a recent but limited altitudinal shift of LBM outbreaks from medium towards higher elevations. We suggest that this altitudinal shift is a consequence of the variable effect of the global warming at the different elevations. Winter warming is expected to affect differently the timing of LBM egg hatch as well as that of larch bud flush, larvae being at present susceptible to emerge whereas no needles are available as food at the former optimal altitude. A better synchronization between larch and LBM may exist at higher elevations.